Evaluation of Merdeka Belajar program of the Kampus Merdeka - Bernadetha Nadeak (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Merdeka Belajar Kampus Merdeka, hereinafter referred to as MBKM. Provide opportunities for students and lecturers to strengthen student-based learning programs. This program also supports students’ soft skills in their learning process, to improve graduates' competencies, both soft skills and hard skills, so that they are more prepared and relevant to the needs of the times, preparing graduates to become superior future leaders of the nation. This paper aims to evaluate the implementation of this program in teaching and learning activities to improve the quality of education. This research was conducted using a quantitative approach. Data collection was carried out by distributing questionnaires through online surveys. Descriptive statistical analysis was used to analyze the data. The results of the study show that students who have participated in the MBKM program provide benefits such as each student can re-explore themselves to find what they like, what they want to develop even more, and what they want to make or create according to their interests and their talents. also provides additional competencies in solving problems, improving soft skills, job search competencies, and post-college preparation competencies. As for the lecturer himself, the lecturer must be able to interfere with himself (self-disruption), continue to improve their competence from time to time (long-life learner) to be able to become a